(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
نفذ البحث في مركز البحوث العلمية الزراعية في القنيطرة، التابع للهيئة العامة للبحوث العلمية الزراعية، خلال ثلاثة مواسم زراعية 2008-2009 -2010؛ أجري البحث على أربعة طرز وراثية لآباء معتمدة هي: Sahelee12، Orient ، Saintpierre، Cherry باتباع تصميم القطاعات العشوائية الكاملة في أربعة مكررات, تم اعتماد اختبار متوسطات الأجيال (Scaling Test and Components of Generation Means). هدف البحث؛ تحديد تأثير السلوك الوراثي، وقوة الهجين في الجيل الأول، والتقهقر الناتج عن التربية الذاتية لأفراد الجيل الثاني؛ على بعض مؤشرات الباكورية (عدد الأيام حتى بداية الإزهار، وعدد الأيام حتى بداية النضج، وطول النبات، وعدد الأزهار/العنقود)؛ تحت ظروف الزراعة المحمية. أجريت تصالبات الآباء بالتهجين نصف التبادلي 4×4، ثم الحصول على نباتات الجيل الثاني F2 والجيل الثالث F3، والتهجين الرجعي للأب الأول BC1، وللأب الثاني BC2. أظهرت النتائج وجود تباينات عالية المعنوية بين عشائر كل هجين لكافة المؤشرات المدروسة, باستثناء عدد الأيام من الزراعة حتى النضج. فقد أظهر الهجينان ((Orient × Cherry, (Sahelee12 × Cherry)؛ أعلى قيمة سالبة مرغوبة لقوة الهجين الوراثية بدلالة إحصائية معنوية؛ في عدد الأيام حتى بداية الإزهار بلغت( 17.31 - , 10.57-) % على التوالي. بينت الدراسة وجود تدهور معنوي لقوة الهجين في الجيل الثاني، متوافق الاتجاه مع قوة الهجن في غالبية الهجن، ولجميع الصفات المدروسة، حيث بلغت قيمة التقهقر (-14.73 %) في الهجين ((Orient × Cherry لصفة عدد الأيام حتى بداية الإزهار. لقد تراوحت نسبة التقهقر ما بين البسيطة والمتوسطة والقوية. كما أظهرت النتائج الأثر التراكمي، والسيادي، والتفوق في توريث صفات الباكورية عند غالبية الهجن، مع سيادة نمط التفوّق التكراري (سيادي × سيادي). This research was carried out at the Center of Agricultural Research in AL Qunaytirah, General Authority for Agricultural Scientific Research during three growing seasons 2008, 2009 and 2010 using four parental genotypes (Sahelee12, Orient, Saintpierre and Cherry) by a randomized complete block design in four replications and based on the Scaling Test to analyze the components of generation means. The study was to determine the effect of behavioral genetics, heterosis in first filial F1 and inbreeding regression in F2 of earliness indicators in green house tomatoes, including the number of days until the beginning of flowering, the beginning of maturity, plant height and number of flowers per cluster. Chiasmata parents was then conducted by half-diallel crossing scheme 4x4; to obtain F1 for all crosses, so as to get from all of them the F2, F3, BC1 and BC2 generations. The results showed high significant differences between the clans of each hybrid in the studied indicators, regarding the days until maturity. The hybrids (Orient × Cherry) and (Sahelee12 × Cherry) gave the highest negative significant values of heterosis in the number of days until the beginning of flowering (-17.31 , -10.57) %, respectively. The study demonstrated a significant inbreeding deterioration in the second generation, compatible with the direction of heterosis in most crosses for all studied traits, as the value of inbreeding deterioration (-14.73%) in the hybrid (Orient × Cherry) for the number of days until the beginning of flowering. The proportion of regression ranged from simple to medium and strong. Reaction genotype analysis of generation means revealed the contribution of the three genotype effects ( additive, dominance and epistasis) in inheriting earliness indicators in most of the crosses, with the predominance of duplicate type of epistasis (dominance x dominance).